Pengembangan Media Bantu Edukasi Hewan Di Sekitar Kita Menggunakan Augmented Reality Berbasis Mobile - Gerald (Jurnal Inovasi Informatika, 2022)
Hewan Di Sekitar Kita is a media education based on Android that aims to educate toddlers to learn about the animals around their environment. The media is created with the Waterfall method and systematically implemented with Unity app and Vuforia that uses Augmented Reality to display animal objects in 3D. With the creation of this media, it is hoped that it could help toddlers in learning the animals thoroughly.